(untitled) (Heritage, 2020)
The paper presents the results of research that included comparative study of the place and role of female characters in selected and representative comedies by serbian comedigrapher Branislav Nušić (eng. MP, Suspicious person, Mrs Minister, Bereaved family, Dr, Deceased; srb. Народни посланик, Сумњиво лице, Ожалошћена породица, Др, Покојник, Власт) and bulgarian comedigrapher Stefan Kostov (eng. Gold mine, Golemanov, Grasshoppers, Nameless comedy; blg. Златната мина, Големанов, Скакалци, Комедия без име) in order to find similarities and differences in the process of comedigraphic shaping of female characters in the work of these two authors. The subject of the research was viewed primarily from a literary-theoretical point of view, and the dominant methods of study were comparative and analytical-synthetic. During the research, there was a differentition of female characters in accordance with their motivational structures, psychological assemblies and the nature of the place and the role they play in the social environment in which they are located. Therefore, we can distinguish female characters who live in the province and who are fully representative of the small-town spirit, female characters who live in the capital and are a symbol of the modern age and female characters who dwell in the capital, but in fact, deeply down still carry a small-town view of the world. The structure of this paper is in line with this distinction. Conclusions made at the end of the study show that the representation of female characters in analyzed comedies of both comedigaphers is highly similar in its nature.